The stimulation of thought during the Physical Education class in students of the primary education career(Original) (Revista científica Olimpia, 2020)
Physical Educations a subject has been and should be an essential means for the integral education of the youth. The educational practice and the systematic knowledge in young people have demonstrated that physical development impacts, a port from health, the intellectual performance and the achievement of the essential skills for leavening.The fundamental problem of the present work lies on the fact that the discipline and subject programs of the physical Education Curriculum E do not show in the physical Education lesson, the didactic procedure for the stimulation of the thought qualities  Independence and Flexibility  on the students of the Primary Education Major. For that reason, the existing didactic strategies lack the specific actions in the dynamics of the Physical Education, showing weaknesses in the didactic conception of formation, teaching and development process in Physical Education.The main intention of the work is aimed at elaborating a didactic strategy supported on a conception of the same nature, which considers the stimulation of the qualities independence and flexibility in the Physical Education discipline in correspondence to the professional Model.
Keywords: thinking stimulation; Didactic strategy; Independence quality; Flexibility quality